Evaluation of clinical and financial outcomes of a new no‐sting barrier film and barrier cream in a large UK primary care organisation. Issue 6 (27th July 2012) - Stephen‐Haynes, Jackie; Stephens, Claire
<x xml:space="preserve">Abstract</x> The study involves 95 subjects within a UK Primary Care Organisation and was undertaken in two arms. The objective was to determine the clinical outcomes and clinical acceptability of a newly available range of no‐sting barrier film and no‐sting barrier cream products offering significant financial benefits. The importance of undertaking this study is underpinned by evidence in the literature relating to the use of no‐sting barrier preparations within clinical practice. The first part of the study (arm 1) involved extensive evaluation of either the film or cream barrier in 36 patients and was compared to existing standardised barrier protection care within the organisation. The results indicated that the new product range met all the criteria for formulary inclusion and following this the barrier range was further evaluated in arm 2, 33 patients with barrier cream and 26 patients with barrier film. The entire study was conducted over a 3‐month period with patient treatment lasting a minimum of 2 days to a maximum 4‐week period adhering to the agreed evaluation protocol as approved by clinical governance. In arm 1 (n = 36), the clinical expectation of the product was met in 32 cases relating to ease of use, conformability, no‐sting, quick drying, ease of absorption, compatibility with devices, frequency of application, prevention and management including visual skin improvement resulting in a recommendation for formulary listing in 31 of 36 cases. In arm 2 (n = 59), barrier film and barrier cream performance was consistently rated same as, better than or much better than the existing barrier used. A formulary listing recommendation was made in 51 of 59 cases.